A focus group study of older adults' perceptions and preferences towards web-based physical activity interventions. (2nd July 2020) - Alley, Stephanie J; Samra, Pamela; Rebar, Amanda L; Schoeppe, Stephanie; Parkinson, Lynne; Power, Deborah; van Uffelen, Jannique G Z; Schneiders, Anthony; Vandelanotte, Corneel
ABSTRACT: Objective: To explore older adults' perceptions and preferences for web-based physical activity interventions. Participants: Adults 65+ years were recruited via telephoning randomly selected households in Central Queensland, Australia. Methods: Six focus groups were conducted with a total of 46 adults 65+ years. Data were analyzed by qualitative content analysis. Results: This group of older adults liked websites that have links to information and included instructional videos and disliked websites that were hard to navigate. Many participants did not express an initial interest in web-based physical activity programs. The most common reason was that they did not have a computer or adequate internet connection. Some participants said they would be interested if it included a structured exercise program. When asked about preferences for web-based physical activity programs, this group preferred them to be simple and not cluttered, to include personalized advice, to include reminder check-ins and the ability to review goals after illness or injury. The most common preference for personalized advice in web-based interventions was that the information needs to be tailored to their existing injuries and illnesses. Conclusion: The findings from this study will inform the design of future web-based interventions specifically tailored to the needs of older people.